2018
DOI: 10.2147/dddt.s179427
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of nintedanib for severe idiopathic pulmonary fibrosis: a single-center retrospective study

Abstract: IntroductionThe INPULSIS-ON trial demonstrated that nintedanib reduced decline in forced vital capacity (FVC) and low pulmonary function (%FVC < 50%) of patients with idiopathic pulmonary fibrosis (IPF). However, there is no sufficient evidence in real world.ObjectivesReveal the utility and adverse events of nintedanib for severe IPF patients.MethodsThis was a single-center retrospective study. Patients who met the eligibility criteria of the INPULSIS trial (%FVC ≥ 50%; %DLCO [diffusing capacity of the lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Nintedanib tended to reduce the decline in FVC, even in the FVC � 50% group. Patients who received nintedanib exhibited smaller FVC reductions, compared to patients not prescribed the drug; this was consistent with the findings of previous studies [6,8,9]. The effects of nintedanib in the FVC � 50% group were also comparable to those of previous studies [6,8,9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nintedanib tended to reduce the decline in FVC, even in the FVC � 50% group. Patients who received nintedanib exhibited smaller FVC reductions, compared to patients not prescribed the drug; this was consistent with the findings of previous studies [6,8,9]. The effects of nintedanib in the FVC � 50% group were also comparable to those of previous studies [6,8,9].…”
Section: Discussionsupporting
confidence: 90%
“…In the interim analysis of the INPULSIS-ON trial, patients who experienced adverse events leading to treatment discontinuation were more frequent in the FVC � 50% group [6]. The same tendency has been reported in other studies [8,9]. We consider that nintedanib must be used carefully, but can be used safely even in patients with a low FVC.…”
Section: Discussionsupporting
confidence: 74%
“…Previous analyses of data from the INPULSIS trials have shown that nintedanib has a consistent effect in reducing FVC decline in subgroups of patients with baseline DLco ≤40% versus > 40% predicted [12] and FVC ≤70% versus [14]. A growing body of observational evidence collected in clinical practice suggests that nintedanib is efficacious in reducing disease progression in patients with severe lung function impairment [15][16][17][18][19]. Taken together, these findings support the use of nintedanib in patients with IPF who have advanced disease.…”
Section: Discussionmentioning
confidence: 53%
“…Previous analyses of safety data from clinical trials of nintedanib have shown a consistent safety and tolerability profile across trials and patient subgroups [13,14,23]. Real-world data from clinical practice suggest that the safety and tolerability profile of nintedanib is similar in patients with IPF who have severe disease as in patients with milder disease, but that patients with more severe disease have a higher rate of treatment discontinuation [16,18,24]. This highlights the importance of patient education and proactive management of sideeffects in patients prescribed nintedanib for the treatment of IPF [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…We read with interest the study by Abe et al on the clinical utility of nintedanib in patients with severe idiopathic pulmonary fibrosis (IPF). 1 Based on the retrospective follow-up of 51 patients, the authors concluded that the survival benefit from nintedanib is reduced among patients with severe IPF (n=17) compared with those with mild-to-moderate IPF (n=34), but that the prognosis for patients with severe IPF is significantly better in those who remain on nintedanib for more than 3 months.…”
Section: Dear Editormentioning
confidence: 99%